COMMUNITY PARTICIPATION IN TOLOMATO VILLAGE DEVELOPMENT PLANNING CENTRAL SUWAWA SUBDISTRICT - Sri Destriyanti Tahaku; Sudarsono; Aryati Hamzah (Jurnal Ilmu Manajemen dan Bisnis, 2023)
This research aims to find out the participation of the community in villagedevelopment planning in Tolomato Village of Central Suwawa Subdistrict, andcommunity participation in the implementation of Development in Tolomato Villageof Central Suwawa Subdistrict.The method in this research uses qualitative research methods of research thatintend to understand the phenomenon of what is experienced holistically, and by wayof description in the form of words and language, in a special context to providesolutions or input to problems that are appropriate and related to the problem.The results of the research are: 1) community participation in developmentplanning in Tolomato Village community and the government has both participatedin village development planning although not all communities who participate invillage development planning; and 2) community participation in the implementationof Tolomato Village has been good done by the community in forming villagegovernment to carry out village development in terms of participation in the form ofenergy and energy. Thoughts given by society.